Music Preferences and Language Anxiety among Introverted and Extroverted EFL Students - Suta, I Putu Wirya; Setiyadi, Ag. Bambang; Mahpul, Mahpul (Universitas Pendidikan Ganesha, 2025)
Language anxiety has been recognized as a significant impediment to effective language acquisition, and music may affect this anxiety. This research investigates the correlation between musical tastes and language anxiety in introverted and extroverted EFL students. Data were acquired from 46 students using surveys utilizing a quantitative design. The Eysenck Personality Inventory (EPI) classified participants as introverts or extroverts, while an adapted Foreign Language Classroom Anxiety Scale (FLCAS) assessed language anxiety. The Study of Music Preferences (STOMP) questionnaire was employed to ascertain their favored music genres. SPSS was employed to analyze the data and investigate the correlation between musical preferences and language anxiety among introverted and extroverted students. The results demonstrate that both introverts and extroverts favor